Factors that Influence Students’ Participation in English Speaking Classroom Activities - Sartika Andi Patau (Sintuwu Maroso Journal of English Teaching, 2018)
This study aims to determine the factors that influence participation to speaking English. This research is conducted at Universitas Sintuwu Maroso Poso. This research is qualitative in nature. The subjects are 36 students of English Education Department who enrolled in Speaking course in academic year 2017/2018. Data are taken through interview, questionnaire, and documentation. The results showed that the highest factor affecting students’ participation in speaking English are lack of basic language skills (grammar and vocabulary) and feedback during activities (lecturer to students).Keywords: factors of students’ speaking English, basic language skills, feedback during activities, classroom participation